INNO IT Framework, Innovation in IT Governance - Šimková, Eva (2008)
The main topic of this thesis is IT innovation management which is very up to date theme as a research within the thesis documents. IT innovation should be managed jointly with the IT Governance to support effectiveness of IT and competitiveness of the whole company.